The cytology and morphology of shrub and tree types of Leucaena leucocephala (LAM) de with and its hybrids - De La Viña, Abella C. (Philippine Agricultural Scientist, The (Formerly the Philippine Agriculturist), 1992)
Two chromosome numbers (2n=104 and 112) were observed in the study. Regardless of the origin and plant type, the chromosome number of the species is equal to 104, for Accession 42 from El Salvador (2n=112). The chromosome behavior was generally normal in all the stages. Univalents and multivalents were present at diakinesis but at very low frequency. One to eight nucleoli per nucleus were observed at telophase of both divisions. Cytokinesis occurred after telophase II producing four microspores.